1992
DOI: 10.1007/bf02071517
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants of malignant melanoma

Abstract: The personal experience with 5 rare types of malignant melanoma is reviewed to point out some of the practical problems in the diagnosis and management of these tumors. The rare forms discussed are conjunctival, nasal, oral, vulvar, and penile melanomas. All pigmented lesions in the oral cavity, but not the penis or vulva, should be prophylactically excised as lesions in the mouth have a higher malignant potential. Local excision of all 5 forms of primary melanomas, no matter how locally advanced they may be, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…As in other series, the lesions most frequently developed on the mucosa overlying the hard palate 2 , 8 , 10 –12 , 18 . Very often oral mucosal melanoma does not produce troublesome symptoms and sometimes the tumour is found incidentally by a dentist, as was the case with one of the SMU patients 12 , 17 , 18 , 20 …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As in other series, the lesions most frequently developed on the mucosa overlying the hard palate 2 , 8 , 10 –12 , 18 . Very often oral mucosal melanoma does not produce troublesome symptoms and sometimes the tumour is found incidentally by a dentist, as was the case with one of the SMU patients 12 , 17 , 18 , 20 …”
Section: Discussionmentioning
confidence: 61%
“…The penis is a rare site for primary malignant melanoma, occurring much less commonly than vulval melanoma 10 . It accounts for 0.6–1.4% of penile malignancies in most large series 5 , 20 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas some authors recommended an aggresive surgical approach with total amputation of the penis, perineal urethrostomy and radical inguinal, iliac and obturator lymph node dissection (8,9,10). But Stillwell et al, belive that conservative penile surgery (local excision with 3 to 5 cm margin or distal partial penectomy) with an appropriate margin when inguinal nodes are nonpalpable in a patient with thin lesions (less than 1.5 mm) and prophylactic superficial inguinal node dissection for those greather than 1.5 mm 3 thick and most authors agree with these treatment (11,12,13). Some others reported that sentinel lymphadenectomy using radiocolloid mapping and dye localization avoided potential morbidity of bilateral superficial inguinal node dissections and allowed accurate staging for further treatment and prognosis (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The combination chemotherapy consisting of six cycles DTIC, BCNU, cisplatin and tamoxifen gives the best result. The respond rate changes between %15 to %45 (11)(12)(13)(14)(15)(16). There has been reported other treatment options; such as radiotherapy, immunotherapy with BCG, endolymphatic iodine-iodized oil infusion but the result are not superior to chemotherapy (2).…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent conservative treatment, including the amputation of the glans in 6 patients, local excision in 3 and partial penile amputation in 2 (3). They believe that conservative surgery such as local excision or partial penile amputation with appropriate safety margin (3-5 cm), can be performed in superficial lesions (less than 1.5 mm) or associated with superficial bilateral inguinal lymphadenectomy in deeper lesions (greater to 1.5 mm), thus being suitable for melanomas stage T1 or T2 (27)(28)(29). However, lack further evidence for defining the optimal surgical margin for lesions with a thickness between 1 and 2 mm, and it is the current trend to practice banks of 2 cm.…”
Section: Discussionmentioning
confidence: 99%